MONITORING SYSTEM DATA PROCESSING ALGORITHM OF WELD-BONDED COUPLING INSTALLATION OF THE MAIN PIPELINES - G. S. Tymchik; A. A. Podolian (Приборы и методы измерений, 2015)
The algorithm for optimal press-in sessions calculations of self-hardening substance in weldbonded coupling space, considering geometric and strength parameters of the strengthen pipe-line, coupling and self-hardening substance, as well as operational parameters of coupling space layer has been proposed. Optimal pressure creation white coupling space layer forming ensures maximum pipe-line coupling strengthening efficiency.